2013
DOI: 10.1007/s10585-013-9622-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the peripheral blood and bone marrow from untreated advanced breast cancer patients that are associated with the establishment of bone metastases

Abstract: Bone metastasis is an incurable complication of breast cancer affecting 70-80 % of advanced patients. It is a multistep process that includes tumour cell mobilisation, intravasation, survival in the circulation, extravasation, migration and proliferation in the bone marrow/bone. Although novel findings demonstrate the bone marrow microenvironment significance in bone metastatic progression, a majority of studies have focused on end-stage disease and little is known about how the pre-metastatic niche arises in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 78 publications
2
35
0
Order By: Relevance
“…The requirement to maintain bone homeostasis and protect (as much as possible) bone mass and strength, in the face of oncologic treatments that kill tumor cells, is fundamental. Recent studies have described significant negative effects of standard chemotherapeutic agents on bone healing, suggesting that the specific treatments (or the tumor cells themselves) may have altered the behavior and/or differentiated activity of osteoclasts, osteoblasts, and/or osteocytes [106108]. …”
Section: Hallmarks Of Breast Cancer Bone Metastasismentioning
confidence: 99%
“…The requirement to maintain bone homeostasis and protect (as much as possible) bone mass and strength, in the face of oncologic treatments that kill tumor cells, is fundamental. Recent studies have described significant negative effects of standard chemotherapeutic agents on bone healing, suggesting that the specific treatments (or the tumor cells themselves) may have altered the behavior and/or differentiated activity of osteoclasts, osteoblasts, and/or osteocytes [106108]. …”
Section: Hallmarks Of Breast Cancer Bone Metastasismentioning
confidence: 99%
“…By comparing peripheral blood plasma in patients with breast cancer bone metastases to healthy volunteers, Martinez and colleagues found that the plasma from patients can induce trans-endothelial migration of MCF-7 cells (a human breast adenocarcinoma cell line). These findings indicate that there are circulating factors in these patients that may promote intravasation, angiogenesis, survival and EMT of circulating tumor cells [40]. …”
Section: Cancer Invasionmentioning
confidence: 99%
“…Currently, there is a general consensus that MIF promotes tumor growth by several mechanisms; it stimulates cancer cell proliferation by triggering the MAPK/PI3K/Akt pathways, inhibits induction of p53-dependent apoptosis, increases production of vascular endothelial growth factor (VEGF) and inhibits the antitumor immune response (46). Moreover, it modulates metastatic behavior of tumor cells and affects tumor stromal cells (7,8). On the cellular level, MIF is stored in the cytoplasmic compartment and is released in response to several stimuli.…”
Section: Introductionmentioning
confidence: 99%